Discrimination of Two Tetragonula (Apidae: Meliponini) Species in Thailand using Geometric Morphometric Analysis of Wing Venation - Rattanawannee, Atsalek; Duangpakdee, Orawan; Rod-im, Preecha; Hepburn, Randall (Agriculture and Natural Resources, 2015)
Geometric morphometrics is a novel powerful tool for the identification of bee species and subspecies. An application of this method is presented to discriminate two stingless bee species, Tetragonula pagdeni Schwarz, 1939 and Tetragonula fuscobalteata Cameron, 1908, in Thailand based on forewing venation. Nine landmarks were measured from the digitized right forewing of 200 workers (10 bees per colony). Eleven colonies of T. pagdeni and nine colonies of T. fuscobalteata collected from several locations in Thailand were determined. The positions of the groups in the principal component analysis plots revealed that the species are clearly distinct. Multivariate analysis of variance (α = 0.01) showed a significant difference between the bees of the sibling species, producing a high degree of accuracy (96.50%) in the identification of any individual bee of either species. Therefore, it is proposed that geometric morphometric analysis of single wings might be an appropriate first step in the analysis and identification of stingless bees and other insects.